Pengaruh Pengajaran Kitab Ta’limul Muta’allim Terhadap Perilaku Tadzim Peserta Didik - Mukhammad Baihaqi; Beti Malia Rahma Hidayati (Universitas Islam Tribakti Lirboyo Kediri, 2020)
This study is an attempt to determine whether there is an effect of teaching the Book of Ta'limul Muta'allim on the ta'dzim attitudes of class X-I TKJ SMK Darul Ulum Rebalas Grati Pasuruan. The research method used a quantitative descriptive approach with a total population of 157 students and a sample size of 36 students. The data were analyzed using a percentage formula and a simple linear regression formula. The results showed that the teaching of the Book of Ta'limul Muta'allim influenced the attitudes of students' ta'dzim, especially in cultivating respect for others, teachers, friends, parents, glorifying books and other moral values to be used as a basis for studying.